Diagnosis of Obstruction in Epiphora by Dacryocystography - Ghulam Sabir, (Journal of Rawalpindi Medical College, 2009)
Background: To determine utility of radiology in localising the site of obstruction in epiphora. Methods: The study was conducted in Lahore General Hospital, Lahore from 22nd January, 1988 to 23rd June, 1988. All thirty patients included had epiphora. Dacrocystography was done on these 30 patients, 14 males and 16 females who were aged from 6 to 75 years. Results: There was complete obstruction in 28 cases, partial obstruction on 01 and no obstruction in 01 case. The sac duct junction was main site of obstruction in 11 patients followed by lower end of the duct and upper bony cana in l 4 patients in each. Conclusion: Dacryocystography is a simple, safe and standardized diagnostic procedure which easily and accurately defines these obstructions and is less time consuming and less annoying to the patients with practically no complications.